Analisis Peran Pemerintah Daerah Dalam Pengembangan Pariwisata di Kabupaten Muna Provinsi Sulawesi Tenggara - Andhika Purnama Ndongu (Departemen Ilmu Pemerintahan Fisip Unhas, 2026)
Tourism is a strategic sector that plays an important role in promoting regional economic growth, improving community welfare, and preserving cultural and environmental resources. Muna Regency possesses several leading tourist destinations, including Napabale Lake and Walengkabola Beach, which offer significant natural and cultural attractions. However, the development of these tourist destinations still faces various challenges, such as limited infrastructure, supporting facilities, accessibility, and tourism promotion. This study aims to analyze the role of the Muna Regency Government in the development of tourist destinations in Muna Regency. This study employed a qualitative descriptive approach using a case study strategy. Data were collected through in-depth interviews, observation, and documentation. The research informants consisted of officials from the Tourism and Creative Economy Office, tourism destination managers, and local community members around the tourist areas. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results indicate that the Muna Regency Government has played an active role in tourism destination development through efforts to create tourism attractions, provide tourism facilities, improve accessibility, and create tourism-related business opportunities for local communities. The development of tourism attractions has been carried out through destination promotion and the organization of cultural events. The provision of tourism facilities has been implemented through the development of supporting infrastructure, while accessibility improvements have been achieved through infrastructure enhancement and easier access to tourist destinations. In addition, the government has encouraged community participation in tourism-based economic activities. Nevertheless, tourism destination development still faces challenges, including inadequate facilities and infrastructure, suboptimal accessibility, and tourism promotion efforts that require further improvement.